Effect of water soluble carriers on dissolution enhancement of aceclofenac - Dahiya, Sunita; Kaushik, Atul (Asian Journal of Pharmaceutics (AJP), 2014)
The solid binary systems of aceclofenac (AC) with Î²-cyclodextrin (Î²CD) were prepared by co-grinding, kneading, and co-evaporation, and with PEG 6000 were prepared by the melt-solvent method in 1:1 and 1:2 molar and weight ratios, respectively.The phase solubility study with Î²CD suggested BS type of curve with a possibility of 1:1 inclusion complex.The solid systems were characterized by in vitro release studies, DSC, and SEM.The results of solid state studies revealed that AC was completely dissolved in the carrier matrix in case of the melt-solvent method, which suggested the possible formation of solid solution with AC to be existed in an amorphous state. All the binary systems exhibited improved dissolution as compared to pure drug. However, the best dissolution enhancement was achieved with the binary system AC: PEG 6000 in 1:2 weight ratio using the melt-solvent method which was subjected to tablet preparation by direct compression.The tablets so compressed complied with in-house and compendial specifications. The in vitro dissolution test was carried out for the formulated tablets and three popular marketed brands of conventional AC tablets. None of the commercial brands showed complete drug release but the formulated tablets exhibited almost complete drug release within 50 min.The dissolution data were further characterized using model-independent parameters DP30, DE50, t50%, similarity factor f2 and difference factor f1. The tablets formulated incorporating the AC: PEG 6000 (1:2) binary system displayed significantly improved dissolution profile as compared to existing immediate release commercial tablets.